O cinema de animação contemporâneo: o diálogo estético e subjetivo entre o animador e o objeto animado - Magalhães, Brenno Levi de Sousa (2023)
This research addresses aesthetic and sociocultural aspects of contemporary animation cinema in Brazil. It emerges from the intersection of the animator's subjective memories and the audiovisual creation process of the series As Memórias de Aryan (MAGALHÃES, 2022). As an investigation in audiovisual arts associated with an authorial creation process, the main goal is to reflect aesthetically on the development of an animated work for children, its characters, and the cultural universe of the Northeast, from the initial sketch to the final artwork, considering the creator's framework within the perspective of Afro-Latin American Studies (EVARISTO, 2018; FERREIRA, 2020; HALL, 2016; NASCIMENTO, 2018; SODRE, 2020). The research and creation protocol was guided, on one hand, by the mapping of recurring elements in the global history of animation (CHOLODENKO, 1991; JONES, 2015), considering the steps derived from the technique of 2D full-frame animation (frame-by-frame drawing) (ALGAR, JACKSON, SHARPSTEEN, 1940; MINKOFF; ALLERS, 1994, MIYAZAKI, 2001) that allowed for the construction of the structure as an animated series. On the other hand, it was guided by auto-ethnographic research methodology, which considers the field diary as a source of analysis, highlighting the challenging process of developing the animated segment with the character Aryan. The protocol, encompassing landscapes from the interior of the Northeast such as the forests of the Ceará hinterland or the Galinha Choca of Quixadá (CE), and cultural expressions like Maracatu, Bumba meu Boi, São João, among others, enabled an aesthetic reflection on the potential of audiovisual and its visual resources for children (URBES, 2012) as a powerful affirmative action. It also emphasized the need for the valorization of characters associated with Afro-Indigenous traditions of the Northeast, contributing to the anti-racist struggle within the Brazilian animation circuit.